PERTIMBANGAN HUKUM HAKIM TERHADAP PERKARA DISPENSASI NIKAH (Studi Penetapan Pengadilan Agama Kelas 1-A Pontianak Nomor 42/Pdt.P/2019/PA.Ptk) - Nugrahanto, Nugrahanto; Haliyah, Dahlia; Fadhil, Moh. (Al-Usroh, 2022)
The purpose of this study is to find out what are the basic sociological considerations and what factors cause sociological considerations to judge the considerations of the Religious Court Class 1-A Pontianak, in granting or rejecting the case of the marriage dispensation. Researchers use qualitative research methods with the type of field research (field research), namely research to solve problems and find theories based on verification of data collected in the field. The normative juridical approach, namely legal research conducted by examining library materials or secondary data as the basis for research, by conducting a search on regulations and previous research relating to the problem under study. The results of the study show that: the basis of sociological considerations is to maintain or prevent a bigger problem from occurring, according to the fiqh rule that preventing damage is prioritized over bringing good, this pregnant woman candidate cannot be separated from the basic considerations by the judges even though it is not stated in the determination of considerations , also do not merely become pregnant as a marriage dispensation granted. There are several factors of sociological consideration of the judges of the Pontianak Religious Court class 1-A in determining the case of marriage dispensation. Among other things: the circumstances, the closeness between the prospective husband and wife and the agreement or agreement on the rights of a child.